Modelos 3D em crochet como ferramentas multifuncionais na comunicação da ciência - Alves, Ana Vilas (2017)
Population ageing is one of the most significant social transformations of the twenty-first century, with implications for nearly all sectors of society. Ageing is in fact the main risk factor for developing dementia and according to the United Nations is probably the most challenging issue of present society. Creative arts such as crochet are not only an occupational therapy which develops finemotricity in youngers and delays its decay in elderly people, but also a way of breaking elderly isolation, of keeping seniors cognitively active and of increasing intergeneration relationships. Moreover, crochet models can be used to help visualize mathematical formulas and biological concepts, which otherwise would be rather difficult for the nonspecialized public. People cannot only see and touch the models, but also learn to make their own. Since 2012, STOL – Science Through Our Lives, a science communication project from University of Minho, has been actively engaged in promoting non-formal science education. A few examples include projects with schools, museums, science fairs and other contexts, as well as the organisation of exhibitions, workshops, seminars, and hands-on activities that bring science to society in an appealing and comprehensive way. Coral reefs, human brains, Petri dishes with microbial growth and fractal fern leaves are some of the 3D-models that STOL has produced in crochet (some on request from science museums and science investigation institutions), combining Biology, Mathematics, Geometry, colour and fun. STOL is also responsible for promoting exhibitions and workshops for various audiences, from young people to elderly, from lay people to mathematics teachers. These non-formal ways to present science have also been used for public engagement activities on topics such as environmental education and brain research. In the present work all these stories will be shared, including the one of the brain in crochet that travelled from Belgium to the UK via Portugal to be presented at the Plymouth Memory Walk event from the Alzheimer’s Society, October 2016, and that helped to break the ice and make people ask questions related with dementia research carried out at the University of Exeter.